Hospitals in Iran and India, 1500 - 1950s - Speziale, Fabrizio (Iran studies, 2012)
Hopitaux et medecins avicenniens en Iran a l'epoque safavide [Avicennian Hospitals and Physicians in Safavid Iran] / Hasan Tadjbakhsh -- Hospitals in Safavid and Qajar Iran : An Enquiry into Their Number, Growth and Importance / Willem Floor -- Des particuliers au service du peuple : Le role des vaqf dans la fondation d'hopitaux en Iran au debut du XXe siecle [Individuals Serving the People : The Role of Vaqf in the Establishment of Hospitals in Iran at the Beginning of the 20th Century] / Omid Rezai -- Together and Apart : Catholic Hospitals in Plural Goa / Cristiana Bastos -- Tradition et reforme du dar al-sifa au Deccan [Tradition and reform of the dar al-sifa in the Deccan] / Fabrizio Speziale -- Healing the People and the Princes : Hospitals, Hakims and Doctors in Bhopal / Claudia Preckel -- Hamdard, How to Share Pain in a Muslim Way / Anna Vanzan -- Glossary -- List of Abstracts